Assessing the sources and dynamics of organic matter in a high human impact bay in the northern Beibu Gulf: Insights from stable isotopes and optical properties - Lu, Xuan; Lao, Qibin; Chen, Fajin; Zhou, Xin; Chen, Chunqing; Zhu, Qingmei (Frontiers in Marine Science, 2022)
Severe human activities in coastal areas have greatly impacted the sources and biogeochemical behaviors of organic matter (OM), including particulate OM (POM) and dissolved OM (DOM). However, few studies have incorporated the indices of POM and DOM to address this issue. Here, a dataset of the combination of stable isotopes of carbon and nitrogen in POM and the optical properties of DOM was presented in Xi Bay, a semi-enclosed bay with a highly developing industrial port in Beibu Gulf, South China, to reveal the origin, distribution, and fate of OM during the rainy season. In the upper bay, depleted δ13C suggested that particulate organic carbon (POC) mainly originated from terrestrial sources. However, the negative relationship between chromophoric DOM (CDOM) and particulate nitrogen (PN) suggested that bacterial-mediated decomposition of POM may be the primary source of CDOM. The negative correlation between humic-like fluorescent components (C1 and C2) and salinity suggested that those two components were mainly affected by terrestrial input. The significant correlation between the protein-like component (C3) and Chl a suggested that C3 was mainly derived from phytoplankton production in the upper bay. In the lower bay, the increase of δ13C values indicated an increased contribution of marine POC. The high levels of CDOM may be due to the decomposition of marine (fresh) POM. However, the low levels of C1 and C2 might be affected by dilution with seawater, and the increased levels of the protein-like C3 were due to enhanced primary production. In addition, the enhancement of δ15N values in both the upper and lower bays indicated serious nitrogen pollution in the bay. This study highlights that biological production fueled by excess nutrients is the dominant OM dynamic process in the bay with high human impact in Beibu Gulf.